Pengukuran Kinerja Supply Chain Management dengan Metode Green SCOR - Adelino, Muhammad Ilham; Farid, Mohammad; Fitri, Meldia; Febry, Muhammad (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The background of this research is the demand for raw materials and the number of sales targets in UMKM Kerupuk Nasi Pak Tatang which have not been fulfilled and the level of product defects which is still high. The research purpose is to determine the performance measurement of supply chain management (SCM) and evaluate the performance measurement based on the lowest score. The method used is the Green SCOR method for determining performance measurements. Data in the form of filling out questionnaires by business owners, the amount of raw materials, the amount of production per month, and the number of defective products. The results showed that the final total value of the Green SCOR performance was 47,066 (marginal level category). Indicators that have a low score are source reliability (number of suppliers according to criteria), deliver responsiveness (length of time for ordering until goods arrive), deliver flexibility (time needed to place additional orders), and return responsiveness (number of complaints received by companies about products). The evaluation given for the number of suppliers is that the company must be able to evaluate each supplier by providing an assessment of the performance results with the AHP method. Evaluation of the length of time for orders to arrive and time for reorders to forecast raw material requirements to optimize order time. The final evaluation for the number of complaints is to provide complaint submission facilities that can be evaluated periodically using the PDCA approach (plan, do, check, action).